Formation of V6O11@Ni(OH)2/NiOOH hollow double-shell nanoflowers for the excellent cycle stability of supercapacitors. Issue 10 (26th February 2021) - Zhang, Qi; Zang, Qian; Shi, Qiqi; Xiao, Zhenyu; Wang, Kun-Peng; Zong, Lingbo; Wang, Lei
Abstract : The rational design of multi-shelled hollow structured electrode materials is of great importance and has met with fundamental challenges in recent years. Abstract : The rational design of multi-shelled hollow structured electrode materials is of great importance and has met with fundamental challenges in recent years. Herein, we demonstrate a combination approach of self-templating and sacrificial templating method for synthesizing double-shelled hollow nanoflower-structured V6 O11 @Ni(OH)2 /NiOOH. Firstly, highly uniform vanadium-glycerate (VG) solid nanospheres are controllably synthesized and employed as the template, then Ni(OH)2 /NiOOH nanosheets grow vertically on it, following with VG solid nanospheres changing to the V6 O11 hollow structure. By controlling the amount of Ni(OH)2 /NiOOH nanosheets, the optimized V6 O11 @Ni(OH)2 /NiOOH-6 (VN-6) delivers high performance for supercapacitors. Specifically, the specific capacitance of VN-6 is 1018.2 F g −1 at the current density of 1 A g −1 and the energy density is 24.3 W h kg −1 at the power density of 850 W kg −1 . Impressively, an outstanding cycling stability of over 120% specific capacitance retention can be obtained after 5000 cycles in the three-electrode and two-electrode systems. The excellent performance can be ascribed to the compositional and structural advantages.